In vitro biomechanical comparison of six different fixation methods following 5-mm sagittal split advancement osteotomies - Oguz, Yener; Watanabe, E.R.; Reis, José Maurício dos Santos Nunes [UNESP]; Spin-Neto, Rubens; Gabrielli, Marisa Aparecida Cabrini; Pereira Filho, Valfrido Antonio [UNESP] (Elsevier, 2015)
The sagittal split ramus osteotomy (SSRO) is a surgical technique used widely to treat many congenital and acquired mandibular discrepancies. Stabilization of the osteotomy site and the potential for skeletal relapse after the procedure are still major problems. The aim of this study was to compare the mechanical stability of six methods of rigid fixation in SSRO using a biomechanical test model. Sixty polyurethane replicas of human hemimandibles were divided into six groups. In group I, the osteotomies were fixed with two four-hole titanium miniplates; in group II, with one four-hole miniplate; in group III, with one four-hole miniplate + a bicortical screw; in group IV, with a grid miniplate; in group V, with a four-hole locking miniplate; and in group VI, with a six-hole miniplate. A linear load in the premolar region was applied to the hemimandibles. The resistance forces (N) needed to displace the distal segment by 1, 3, and 5 mm were recorded and the data transmitted from the load cell to a computer. One-way analysis of variance with Tukey's post hoc test was performed to compare the means between groups. For the three displacement conditions, there was a strong tendency for the 2.0-mm plate + screw and the grid plate to have higher values.
Keywords: Sagittal split ramus osteotomy; Fixation; Polyurethane hemimandibles; Biomechanical test